2018
DOI: 10.1159/000495706
|View full text |Cite|
|
Sign up to set email alerts
|

Interleukin-35 Expression in Non-Small Cell Lung Cancer is Associated with Tumor Progression

Abstract: Background/Aims: Lung cancer continues to be the leading cause of cancer related deaths worldwide due to its high incidence, malignant behavior and lack of major advancements in treatment strategy. The occurrence and development of lung cancer is closely related to inflammation. Thus, we conducted the present study to investigate the effects of IL-35 (Interleukin 35), a newly identified anti-inflammatory factor, on non-small cell lung cancer (NSCLC), which accounts for about 85% of all lung cancers. Methods: W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Thus, IL-35 in combination with chemotherapy could be a useful treatment for colon cancer. Similar studies showed that IL-35 plays an inhibitory role in human NSCLC and colon cancer cells by suppressing cell migration and colony formation [188,189]. In hepatocellular carcinoma (HCC) patients, IL-35 expression was significantly reduced in patients with advanced cancer as compared to early stages.…”
Section: Il-35 In Inhibiting Tumor Growthmentioning
confidence: 76%
“…Thus, IL-35 in combination with chemotherapy could be a useful treatment for colon cancer. Similar studies showed that IL-35 plays an inhibitory role in human NSCLC and colon cancer cells by suppressing cell migration and colony formation [188,189]. In hepatocellular carcinoma (HCC) patients, IL-35 expression was significantly reduced in patients with advanced cancer as compared to early stages.…”
Section: Il-35 In Inhibiting Tumor Growthmentioning
confidence: 76%
“…In human patient samples, decreased IL-35 expression was observed in cancer sites compared to non-cancer sites. Through the use of NSCLC cell lines, this study demonstrated that IL-35 treatment resulted in suppressed beta-catenin expression and decreased migration, invasion, and proliferation of the cancer cells (148). Therefore IL-35 may behave similarly to IL-27 to have divergent roles in cancer progression that may be dependent on cancer type, stage, and TME landscape.…”
Section: Il-27 Il-30 and Il-35: Influencing Cancer Developmentmentioning
confidence: 92%
“…The primary function of IL-35 within the TME appears to be in favor of a pro-tumor immune environment. In contrast to the work discussed above, Sun et al outlined a potential anti-tumor role for IL-35 in NSCLC (148). In human patient samples, decreased IL-35 expression was observed in cancer sites compared to non-cancer sites.…”
Section: Il-27 Il-30 and Il-35: Influencing Cancer Developmentmentioning
confidence: 97%
“…It has been illustrated that IL-35 inhibits T cells proliferation and transforms T cells into suppressive inducible Tregs ( 3 ). Recently, some studies have demonstrated the expression of IL-35 is correlated with tumor progression, including breast cancer, NSCLC and prostate cancer ( 5 , 6 , 13 ). Moreover, our previous study found that IL-35 is expressed highly in the peripheral blood and tumor tissues of patients with LSCC ( 8 ).…”
Section: Discussionmentioning
confidence: 99%